New species and records of Orchidaceae from Costa Rica. IV. - Belfort-Oconitrillo, Noelia (2024)
The fourth release of the series “New Species and Records of Orchidaceae from Costa Rica” documents and illustrates 17 taxa of the Costa Rican orchid flora. The new species records belong to the subtribes Pleurothallidinae (9 spp.), Maxillariinae (3 spp.), and Oncidiinae (2 spp.), including the description of two new species in Pleurothallis and Telipogon. Two new forms are described for Isochilus latibracteatus (Ponerinae) and Masdevallia striatella(Pleurothallidinae), and their differences from the typical forms are discussed. Additionally, the first record of a naturalized population of Phalaenopsis stuartiana(Aeridinae) in Costa Rica is discussed. Detailed descriptions, based on selected Costa Rican material, are included for all taxa, along with illustrations and/or Lankester Composite Digital Plates (LCDP). Information on their etymology, distribution, habitat, phenology, and distinguishing features compared to morphologically similar species is also provided. Finally, following the publication of the most recent Costa Rican orchid catalogue, we have identified some omissions and other new species described, which are discussed here. The orchid flora of Costa Rica now includes 1695 species and nine forms.